Autoantibodies immuno-mechanically modulate platelet contractile force and bleeding risk - Oluwamayokun Oshinowo; Renee Copeland; Anamika Patel; Nina Shaver; Meredith E. Fay; Rebecca Jeltuhin; Yijin Xiang; Christina Caruso; Adiya E. Otumala; Sarah Hernandez; Priscilla Delgado; Gabrielle Dean; et al. (Nature Communications)
Abstract Altered mechanotransduction has been proposed as a putative mechanism for disease pathophysiology, yet evidence remains scarce. Here we introduce a concept we call single cell immuno-mechanical modulation, which links immunology, integrin biology, cellular mechanics, and disease pathophysiology and symptomology. Using a micropatterned hydrogel-laden coverslip compatible with standard fluorescence microscopy, we conduct a clinical mechanobiology study, specifically focusing on immune thrombocytopenia (ITP), an autoantibody-mediated platelet disorder that currently lacks a reliable biomarker for bleeding risk. We discover that in pediatric ITP patients (n = 53), low single platelet contraction force alone is a “physics-based” biomarker of bleeding (92.3% sensitivity, 90% specificity). Mechanistically, autoantibodies and monoclonal antibodies drive increases and decreases of cell force by stabilizing integrins in different conformations depending on the targeted epitope. Hence, immuno-mechanical modulation demonstrates how antibodies may pathologically alter mechanotransduction to cause clinical symptoms and this phenomenon can be leveraged to control cellular mechanics for research, diagnostic, and therapeutic purposes.